Vertical jump measurement results using the VJMeter and standing board: Observation of the VJMeter accuracy level - Supriyadi Supriyadi; Moch Yunus; Lokananta Teguh Hari Wiguno; Abi Fajar Fathoni; Indi Ni'matur Rohmatika (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
In various sports activities, tools are essential to facilitate the process, including vertical jump measurement, which is frequently performed across different sports. The necessity for practical, user-friendly, and highly accurate tools is paramount for measuring vertical jumps in diverse settings, each with unique constraints. This research aims to ascertain the accuracy level of the VJMeter device developed for vertical jump measurements. Employing a quantitative approach, the study compared vertical jump measurements obtained from a standing board and the VJMeter device. The study involved 10 students from the Physical Education program who participated in basketball. The research variable comprised vertical jump measurement results, categorized into two independent samples: measurements from the standing board and the VJMeter device. Data analysis was conducted using the Mann-Whitney test in SPSS version 25. The results indicated a p-value of 0.987, exceeding 0.05, signifying no significant difference between vertical jump measurements obtained from the standing board and the VJMeter device. Therefore, it can be concluded that the VJMeter device demonstrates a reliable level of accuracy for measuring vertical jumps.